Habermas : Introduction and Analysis - Ingram, David, 1952- (Book collections on Project MUSE., 2010)
Ingram's book addresses the entire range of Habermas's social theory, including his most recent and widely discussed contributions to religion, freedom and determinism, global democracy, and the consolidation of the European Union. Recognizing Habermas's Position as a highly public intellectual, lngram discusses how Habermas applies his own theory to pressing problems such as abortion, terrorism, genetic engineering, immigration, multiculturalism, separation of religion and state, technology and mass media, feminism, and human rights. He also presents a detailed critical analysis of Habermas's Key claims and arguments --Book Jacket.